Motivational Activities for Intermediate Students Considering Their Perceptual Learning Styles: Design of a BA Thesis - Villaseñor, Samuel; Castillo, María; Christiansen, Martha; Murga, Norma (CIEX JOURNAL, 2017)
This article presents the design of a study that makes an attempt to explore the relation between the students’ learning through activities based on perceptual learning styles and the impact that those learning activities have on students’ motivation to learn English. The context of the study was Centro de Idiomas Extranjeros (CIEX) and the participants were eight EFL intermediate level students with ages ranging from 13 to 18 years. The research was developed using the mixed methods approach, since it involves characteristics of qualitative and quantitative approaches. The instruments used for gathering data were: a questionnaire regarding perceptual learning style preferences, a test battery regarding motivation and attitudes towards learning English, a weekly observation format regarding researcher’s direct observations on students’ motivation to learn English, and an interview guide regarding students’ perceptual learning styles preferences and motivation. The analysis of the theory related to the main topics of the study, the research methodology, and the results and discussion will be presented in another article.